2016
DOI: 10.1111/apa.13322
|View full text |Cite
|
Sign up to set email alerts
|

Infants under two months of age with urinary tract infections are showing increasing resistance to empirical and oral antibiotics

Abstract: Resistance to antibiotics challenges empirical therapy and compromises oral treatment options in young infants with UTIs. Antimicrobial resistance patterns should be monitored in infants to determine appropriate empirical antibiotic therapy protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
1
5
1
1
Order By: Relevance
“…15 Previous studies have demonstrated the significant differences between Enterococcus and gram-negative pathogens in febrile infants, including differences in gestational age, resistance patterns, pyuria, and urinary tract abnormalities. 6,14,16,17 Our findings of variation in LOS compared with gram-negative pathogens substantiates previous findings differences in clinical course of Enterococcus UTIs. 16…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…15 Previous studies have demonstrated the significant differences between Enterococcus and gram-negative pathogens in febrile infants, including differences in gestational age, resistance patterns, pyuria, and urinary tract abnormalities. 6,14,16,17 Our findings of variation in LOS compared with gram-negative pathogens substantiates previous findings differences in clinical course of Enterococcus UTIs. 16…”
Section: Discussionsupporting
confidence: 91%
“…6 Despite evolving resistance patterns to UTI, susceptibility to empiric treatment remained very high across all clinical groups. 6,14 Our findings of satisfactory empiric coverage of young infants with UTIs mirror those of febrile infants and infants with febrile UTI <90 days of age. 6…”
Section: Discussionmentioning
confidence: 57%
“…Few studies are available on patients aged under 3 months. Segal et al reported that E. coli was isolated in 76.4% of UTIs that occurred in infants younger than 2 months, followed by Klebsiella pneumoniae and Enterobacter cloacae in 13.8% and 1.9% of cases, respectively [ 33 ]. Pseudomonas aeruginosa was isolated only in 0.9% of infants.…”
Section: Resultsmentioning
confidence: 99%
“…Despite being a natural consequence of antibiotic therapy, resistance to this type of drugs has been growing [2]. A responsibility for increasing resistances has been attributed to an also increasingly easier access to this medication; in addition, this induced a more frequent prescription, most of the times by less informed health practitioners and hence a wider usage in a larger range of infectious conditions [3]. All these sequential facts had favoured the development of microbial strains resistant to the most commonly used antibiotics [2].…”
Section: Introductionmentioning
confidence: 99%
“…All these sequential facts had favoured the development of microbial strains resistant to the most commonly used antibiotics [2]. This upsurge of resistance is a proven fact, shown by its emergence at an earlier age [3], as is the adequacy of the therapeutic decision the current concern of physicians [4]. Simultaneously, there has been a distinct reduction in production of new classes of antimicrobial drugs.…”
Section: Introductionmentioning
confidence: 99%